High Mobility Supports Routing Protocol (HMSRP) in Mobile Ad Hoc Networks - T.Senthil Murugan, Dr; ., . (International Journal of Engineering and Technology, 2018)
Now-a-days wireless communication required for infrastructure less environment due to avoiding centralized data maintenance and fixed infrastructure data transmission because these types of network not supporting in emergency situation like natural disaster, Battle field and so on. But, Mobile Ad-Hoc networks (MANETs) are support the data communication in the above mentioned situations. In MANET, network implementation and maintenance has many emerging research areas like routing, Energy management, Quality of services, etc. Even many types of protocols are proposed and identified in this area but still it is more complex for identifying quality route. One of the most important factors for identifying quality route is â€œMobilityâ€. Many researchers are proposed protocols based on routing with random mobility. In this paper, we propose a new routing protocol â€œHigh Mobility Supports Routing Protocol (HMSRP)â€ which is supporting high mobility. Mobility has to be calculated using directional antennas. This proposed new protocol has supports to identify the location of the node, enhance the fast data transmission and control the fast communication.Â  Simulation results are shown our proposed protocol is produce good results over other protocol.